Completed but unmounted "Star" by A. Stirling Calder and male and female figure medallions by B. Bufano - Cardinell-Vincent:::::::::
Sculptures mounted on sides of Arches of the Rising Sun and Setting Sun. Ninety "Star(s)" were used on Court of Universe.